Salt Metathesis: Tetrafluoroborate Anion Rapidly Fluoridates Organoboronic Acids to give Organotrifluoroborates. (21st February 2023) - Lozada, Jerome; Xuan Lin, Wen; Cao‐Shen, Rosana M.; Astoria Tai, Ruyin; Perrin, David M.
Abstract: Tetrafluoroborate (BF4 − ) has long been used as a spectator counter anion. Herein, we report an unprecedented salt metathesis between a variety of BF4 − salts and a series of organoboronic acids yielding the corresponding organotrifluoroborates. We identified conditions for fast and efficient fluoridation (<1 h) with minimal workup. Fundamentally, this work discloses the proclivity of BF4 − to exchange fluoride atoms with organoboronates, highlighting the lability of BF4 − . Abstract : Tetrafluoroborate anion, considered to be weakly coordinating and relatively inert for organic chemistry applications, readily undergoes salt metasthesis with organoboronic acids to afford the corresponding organotrifluoroborates. Its spontaneous solvolysis in methanol to HF/MeOBF3 − and pH‐dependent aqueous solvolysis as a more general feature, highlight its non‐inertness and reactivity potential for use in organic synthesis.